Methodology and results of phase change material integration in photovoltaic-thermal systems for enhanced energy production in domestic settings: a review - Awai, Kar R.; King, Peter; Patchigolla, Kumar (Elsevier, 2026)
This review explores the use of phase change materials (PCMs) in photovoltaic/thermal (PV/T) systems to improve temperature control and energy storage. It provides a comprehensive overview of current PV/T systems integrated with PCMs, highlighting their potential to increase domestic energy production. The paper covers fundamental principles, benefits, and limitations of PVT technology, the role of PCM applications, and methods of integration. It also examines efficiency gains in power and thermal output, discusses challenges, and suggests future research directions for sustainable energy. Incorporating PCMs into PV/T systems marks notable progress in balancing electrical and thermal efficiencies. Finned serpentine heat exchangers improve heat transfer to PCMs, with more fins increasing surface area and cooling efficiency, while optimised flow rates balance electrical gains against thermal losses. Encapsulation prevents leakage and enhances thermal conductivity. Design factors such as a 25° inclination, insulation, and using dual PCMs in cold regions further improve performance. Economically, PV-T/PCM systems can have shorter payback periods than conventional PV panels if they are used for dual energy and in regions with high solar radiation. However, their viability depends on solar radiation, energy prices, and system costs, which vary by location.
Keywords: Photovoltaic-thermal; Nanoparticles; Phase change material; Organic PCMs; Inorganic PCMs; 40 Engineering; 4009 Electronics, Sensors and Digital Hardware; 7 Affordable and Clean Energy; 11 Sustainable Cities and Communities